ASUHAN KEPERAWATAN PALIATIF PADA Ny. R DENGAN CA MAMMAE METASTASIS PARU DI RUANG JASMINE RUMAH SAKIT Hj. BUNDA HALIMAH BATAM - Liana Liana; Noni Hadiyati; Rahmat Hidayat; Mardiani Mardiani; Serly Mardiah Tullah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Breast cancer with lung metastasis is an advanced-stage condition that causes physical and psychological problems requiring comprehensive palliative care. The purpose of this paper was to describe the implementation of palliative nursing care for Mrs. R with breast cancer and lung metastasis in Jasmine Ward at Hj. Bunda Halimah Hospital Batam. The method used was a case study approach through the nursing process including assessment, diagnosis, intervention, implementation, and evaluation. Assessment results showed acute pain, ineffective breathing pattern, anxiety, imbalanced nutrition less than body requirements, risk of shock, and risk of infection. Nursing interventions included pain management, oxygen therapy, wound care, psychological support, nutritional support, and family education. After 3×24 hours of nursing care, pain and dyspnea decreased, the patient appeared calmer, although several nursing problems were not fully resolved due to disease progression. In conclusion, palliative nursing care can improve comfort and quality of life in patients with breast cancer and lung metastasis.